Análise das propriedades ópticas de antibióticos e o efeito desses antibióticos na terapia fotodinâmica antimicrobiana com azul de metileno: estudo espectroscópico - Salani, Renata (2021)
Due to with bacterial resistance to antibiotics, antimicrobial photodynamic therapy (aPDT) has been gaining more visibility. In the presence of a clinical condition of infection, the gold standard treatment is systemic antibiotic therapy, but local use of aPDT may also be indicated. Despite this association being an interesting strategy to combat microorganisms, little is known about the interaction between photosensitizing agents and antibiotics. In this sense, since the action of aPDT is based on reactive oxygen species, evaluating this production in the presence of the antibiotic is a way to study possible interactions between it and the photosensitizing agent. The main objective of the study was to analyze the optical properties of antibiotics and quantify the production of reactive oxygen species formed by photoactivation of methylene blue (MB) when associated with antibiotics. For this, the values of reflectance and diffuse transmittance of the antibiotics and the absorption spectra of the p-nitrosodimethylaniline probe were recorded when the AM was irradiated with red laser alone or in the presence of antibiotic. Thirteen antibiotics commonly used in hospital routine were studied. There were 720s of irradiation in total, at 660nm, 89mW, with an absorption spectrum recorded every 60s. Data were analyzed and the kinetic constant of the oxidative reaction with p-nitrosodimethylaniline was determined in all cases. Antibiotics showed absorption at the studied wavelengths. The value of the reaction kinetic constant of AM when irradiated in the presence of cefazolin, cefuroxime or meropenem showed an increase when compared to AM alone, while in the presence of amoxicillin, ceftriaxone, levofloxacin, oxacillin, teicoplanin and vancomycin there was a decrease in the kinetic constant in relation to AM. More studies are needed to better understand the results found in the present study.